City and Ecology: Notes Towards an Urban Ecological Politics - Kipfer, Stefan (UnderCurrents: Journal of Critical Environmental Studies, 1995)
Our understanding of urban ecology continues to be informed by the nature ideologies of Social Darwinism, romanticism and scientism which are currently mobilized by political actors for concrete social projects: neo-fascism. eco-capitalism and different variants of environmentalism. Accordingly it is not at all self-evident that the city should provide the site for ecological politics. [...]